Evaluation of responses to energy price changes in the light of primary research among Hungarian enterprises - Baranyi , Aranka; Bélyácz, Iván; Széles, Zsuzsanna; Csernák, József (Acta Carolus Robertus, 2024)
For a business to survive, it is increasingly important to be resilient to shocks caused by the economy, the market and inflation, in addition to financial conditions. Our research was conducted in the second half of 2022, when 184 large and medium-sized enterprises were questioned online. The survey, and the purpose of our study, was to examine how businesses were responding to the rise in energy prices. The pandemic itself has posed challenges for both Hungarian and international businesses, but the emerging energy price shocks have added new challenges. The survey data were processed using SPSS statistical software package. Following the assessment of descriptive statistics, factor analysis was used to examine whether businesses responded differently or in the same way to questions about their operations. After data cleaning, three factors were identified, on the basis of which the enterprises were classified using cluster analysis, and it was then possible to characterise the enterprises at the group level. The factor analysis showed that firms follow a preference order in their short and long term decisions. The majority of the firms in the sample were sensitive to the increase in energy prices, with different responses.